The Woman Artist in Edna St. Vincent Millay’s Poetry - Nikèeviæ-Batriæeviæ, Aleksandra; Kneževiæ, Marija (Armenian Folia Anglistika, 2009)
Edna Millay, a legendary personality, a virtuous and independent woman built her world referring to the complicated issues that have troubled the humanity in the course of the entire history – woman-man relations, sympathy towards the one next to you, devotion towards one’s homeland, etc. These notions underwent transformations and turned into a lyrical world with a universal value consistent with emotions. As Daniel Mark Epstein claims this woman-artist revolts against patterns, hypocrisy, fake eloquence and sentimentalism declaring a violent war against traditional forms of poetry. Through the analysis of several poems selected from the best collections of Edna Millay, the article reveals the hidden world of the woman-artist, her struggle and world vision.